Influence of fast proton irradiation with energies of 12.4 and 12.8 MeV on magnetic characteristics and microstructure changes of superconducting intermetallic compound Nb3Sn. (September 2016) - Degtyarenko, P N; Ballarino, A; Bottura, L; Gavrilkin, S Y; Flukiger, R; Karateev, I A; Kruglov, V S; Latushkin, S T; Scheuerlein, C; Ryazanov, A I; Semenov, E V; Shavkin, S V; et al.
Abstract: Data on magnetization, magnetic susceptibility and microstructure modification of irradiated Nb3 Sn platelets are presented. The irradiation was produced at room temperature by fast protons with the energies of 12.4 and 12.8 MeV with fluencies of 5x10 17 and 1x10 18 cm -2 . Variation of the superconducting transition temperature versus irradiation dose was determined. Temperature dependence of magnetic susceptibility of Nb3 Sn platelet with 160 μm thickness demonstrates several steps corresponding to different superconducting transition temperatures. We supposed that there are layers inside the sample with significantly different radiation damage levels caused by particles movement termination (Bragg peak). It was found that after the irradiation a lot of randomly oriented platelet-like Nb-enriched particles of 0.1-0.5 μm size appear in volumes with maximal damages.